Autoimmune biomarkers in porto‐sinusoidal vascular disease: Potential role in its diagnosis and pathophysiology. (11th July 2021) - Cerda Reyes, Eira; González‐Navarro, Europa Azucena; Magaz, Marta; Muñoz‐Sánchez, Guillermo; Diaz, Alba; Silva‐Junior, Gilberto; Triguero, Ana; Lafoz, Erica; Campreciós, Genís; Orts, Lara; Perez‐Campuzano, Valeria; Seijo, Susana; et al.
Abstract: Background and aims: Porto‐sinusoidal vascular disease (PSVD) is a rare disease that requires excluding cirrhosis and other causes of portal hypertension for its diagnosis because it lacks a specific diagnostical test. Although it has been occasionally associated with autoimmune diseases, the pathophysiology of PSVD remains unknown. The aim of this study was to evaluate the potential role of autoimmunity in the pathophysiology and diagnosis of PSVD. Methods: Thirty‐seven consecutive patients with PSVD and 39 with cirrhosis matched by gender, signs of portal hypertension and liver function were included (training set). By using Indirect Immunofluorescence, ELISA and slot‐blot methods data 22 autoantibodies were identified in patients with PSVD and cirrhosis. Presence of anti‐endothelial cells antibodies (AECA) was assayed by a cell‐based ELISA. Thirty‐one PSVD, 40 cirrhosis patients, 15 patients with splenomegaly associated with haematological disease and 14 healthy donors were included in a validation set. Findings: The proportion of patients with at least one positive antibody was statistically significantly higher in patients with PSVD compared with cirrhosis (92% vs 56%; P  < .01). Specifically, AECA were significantly more frequent in PSVD than in cirrhosis (38% vs 15%; P  = .013). Results were confirmed in the validation set. In the overall population, presence of AECA had a 63% positive predictive value for diagnosing PSVD and a 71% negative predictive value, with a specificity of 94% when the 1/16 level is used as cut‐off. AECA positive serum samples react with a 68‐72 kDa protein of human liver endothelial sinusoidal cells.